Hubungan Faktor Lingkungan Fisik Rumah terhadap Kejadian Pneumonia pada Balita di Kelurahan Bujel Kediri - Hidayah, Hefinka Anevia Nurul (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Pneumonia is an acute infection affecting lung tissue in the alveoli caused by various microorganisms such as viruses, fungi, and bacteria. The physical environment of the house such as temperature, humidity, lighting, density, and the type of wall can be the spread of pneumonia-causing microorganisms. The purpose of this study to determine the relationship between environmental factors home to the incidence of pneumonia in children under five in Kelurahan Bujel Kediri. This research was conducted by design case control with 30 respondents for case and control group. Data were collected through interviews, observations, and measurements. Data analysis using Chi-square test. The results showed that there was no significant relationship between temperature, humidity, and home lighting on the incidence of pneumonia. It is known from the temperature p value = 0,353 (p> 0,05), humidity p value = 1,000 (p> 0,05), lighting p value = 0,606 (p> 0,05), occupancy density pvalue = 0,542 (p> 0,05), and room wall type p value = 1,000 (p> 0,05). Keywords : Pneumonia, children under five years, physical environment of house